Socio-environmental system for the revaluation of textile waste: history of development of a Textile Waste Bank (ModaPalavra e-periódico, 2023)
This article aims to present the development process of a socio-environmental system for the revaluation of textile waste based on Circular Economy, Reverse Logistics and Design for Sustainability. The System, called Textile Waste Bank - BRT, is currently being implemented in a cooperative of collectors of recyclable materials in Londrina - Paraná and was idealized by the DeSIn group (Design, Sustainability and Innovation) of the State University of Londrina in the period from 2017 to 2022. Its objective is to manage industrial and post-consumer textile waste in the region, combining the offer of products and services in its operation. The methodologies used during its development were Case Study, Design Science Research and Action Design Research. The results integrate the contributions of the different research stages and are presented chronologically, allowing the development of systems such as BRT to be replicated by other institutions in other regions of the country.
Keywords: socioenvironmental system; textile waste; textile waste bank